Trabecular bone score in the assessment of bone health in thalassemia major - Di Noto, Martina; Xourafa, Anastasia; Rosso, Rosamaria; Bulla, Anna; Catalano, Antonino; Bellone, Federica; Zanoli, Luca; Buccheri, Enrico; Castellino, Pietro; Gaudio, Agostino (Frontiers in Endocrinology, 2025)
IntroductionThalassemia major (TM) has a significant impact on patients’ quality of life. Osteoporosis and osteopenia are common and important complications, yet they are often underestimated. Their etiology is multifactorial, culminating in reduced bone mass, impaired remodeling, and increased fracture risk. The reported prevalence of osteopenia and osteoporosis in TM is highly variable, reaching up to 90%. The trabecular bone score (TBS) is a relatively recent analytical tool that measures lumbar spine texture on dual X-ray absorptiometry (DXA) images. At present, only limited data are available on its use in TM. The aim of this retrospective study was to assess bone health in TM and to evaluate the TBS as a potential diagnostic and prognostic tool.MethodsEighty-eight adult outpatients with TM (mean age: 41.9 ± 8.9 years) were enrolled. The following parameters were evaluated: laboratory tests, DXA measurements, and thoracic–lumbar spine X-rays (assessed by Genant’s method).ResultsReduced BMD was observed in 96.3% of patients. TBS values were also markedly reduced; however, their performance in discriminating fractures in this cohort appeared to have limited clinical utility.DiscussionThe TBS may be a valuable, non-invasive complementary tool for assessing bone quality alongside BMD, although it does not reliably discriminate between patients with and without fractures. Further investigations are needed to clarify the role of the TBS in predicting fracture risk in TM.